Association of Neutrophil-to-Lymphocyte Ratio with One-Year Mortality in Maintenance Hemodialysis Patients - Amini, Sri Rahmania; Nasution, Alwi Thamrin; Tarigan, Radar Radius (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Chronic kidney disease (CKD) carries a high morbidity and mortality rate, particularly among patients undergoing maintenance hemodialysis (MHD). Inflammation is a key mechanism affecting prognosis, and the neutrophil-to-lymphocyte ratio (NLR) is a simple, accessible marker of systemic inflammation. This retrospective cohort study aimed to evaluate the association between NLR and one-year mortality in MHD patients. A total of 65 adult CKD patients at Adam Malik General Hospital, Medan, from January to December 2024 were included. Demographic, clinical, and laboratory data were obtained from medical records, and NLR was calculated as the neutrophil count divided by the lymphocyte count, categorized as <3.5 and ≥3.5. Associations were analyzed using Chi-square or Fisher’s exact test, with odds ratios (OR) and 95% confidence intervals (CI). The mean age was 48.35 ± 13.43 years, and 66.2% were male. The median NLR was 2.93 (IQR 2.25), with 46.2% ≥3.5. One-year mortality was 30.8%. Elevated NLR (≥3.5) was significantly associated with higher mortality (46.7% vs. 17.1%; p=0.01) and a 4.229-fold higher risk of death (95% CI: 1.36–13.15). High NLR is significantly associated with increased one-year mortality in MHD patients. Routine NLR monitoring may help identify high-risk patients for earlier intervention.